Application of BCI in Muscle Regeneration Tissue - Cao Yaoxian; Zhou Shengkai; Zhao Yunbo (BIO Web of Conferences)
The application of brain-computer interface (BCI) technology in the medical field continues to expand, and the research on muscle regeneration tissue has gradually attracted attention. BCI is a real-time computer system that converts electrical signals into control instructions and can interact with the external environment without the use of the nervous system and muscles. This paper aims to explore the application of BCI in muscle regeneration tissue, including its potential in motor control, rehabilitation therapy, neuromuscular interface, etc. In this research, the advantages and problems of brain-computer interface (BCI) technology pertaining to the promotion of muscle function recovery, the improvement of movement disorders, and the assistance of neuromuscular reconstruction are discussed. This is accomplished by evaluating the interaction mechanism between BCI technology and muscle regeneration tissue. At the same time, the future development direction of BCI in the field of muscle regeneration tissue is also explored. This includes the technical innovation, clinical application, and multidisciplinary collaboration that are all included in this discussion. Patients are anticipated to experience improved rehabilitation and quality of life as a result of the utilization of BCI in muscle regeneration tissue, which offers a novel approach to the treatment of muscle injury and disease.